PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIA 1 MA MUHAMMADIYAH PEKANBARU - Ranti Silvia; Elfis Suanto; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is the difference between the expected achievement and the achieved by students of class XI MIA 1 MA Muhammadiyah Pekanbaru. The proposes of this research are to improve the learning process and to increase mathematics achievement from the students with applied discovery learning model. The form of this research is a class action research which is carried out in two cycles. Each cycle has four meetings and one test. The subject of this research is the students of class XI MIA 1 MA Muhammadiyah Pekanbaru in academic year 2019/2020, which total of participants are 21 students, consists of 7 female students and 14 male students with heterogeneous ability. The instruments used in this research were learning instruments and the instruments of collecting data. The learning instruments used include syllabus, lesson plan, and student work sheets, while the instruments of collecting data were observation sheets and learning mathematic tests. The observation sheets were analyzed in qualitatively, while the students Mathematic tests were analyzed in quantitatively. The data analysis of students and teacher activity showed that the learning process has improved after the discovery learning model being implemented. Most of students were very confidenced and active in learning process, the students are skilled to build their knowledge by their own, hence the learning becomes more meaningful and saved in student’s memory for a long time. The data of the student’s evaluation test showed that the number of students reached the Minimum Mastery Criteria (MMC) increase from the basic score to first test, from first test to second test. The results of this research showed an increasing of students achievement where the basic score 28,51% to the first test 52,4%, the second test 85,7%. For the skills achievement score of the first test 52,4%, the second test 90,5%. Based on data analysis, it can be concluded that the implementation of discovery learning model can improve learning process and increase student’s mathematics achievement at class XI MIA 1 MA Muhammadiyah Pekanbaru.Key Words: Mathematics Achievement, Discovery Learning, Class Action Research